A Meta-Analysis Examining the Effect of E-Book Use on Literacy Outcomes for Students in Grades K–12. Issue 5 (2nd September 2020) - Swanson, Elizabeth; Austin, Christy R.; Stewart, Alicia A.; Scammacca, Nancy
Abstract: To better understand the impact of using e-books on students' reading outcomes, we conducted a meta-analysis of 14 studies with students in grades K–12 published between 2007 and 2018. Findings revealed an average effect size across all studies and reading outcomes of 0.9 that did not differ significantly from zero. There was also no statistically significant difference between e-book and non-e-book conditions on measures of reading comprehension. While these findings present preliminary evidence that e-books may be a viable alternative to traditional print books for supporting students' reading comprehension development, reasons for interpreting these findings with caution are presented.